Kausalitas antara penerimaan daerah dan pertumbuhan ekonomi di Kota Lubuklinggau - Redza Delingga; Taufiq Marwa; Rosmiyati Chodijah (Jurnal Ekonomi Pembangunan, 2016)
This study aims to identify the relationship between regional revenues through hotel and restaurant taxes and market retribution and economic growth in trade, hotels and restaurants. This study uses secondary data collected from the Central Bureau of Statistics (BPS) and the Office of Revenue, Assets and Financial Management (DPPKAD) of Lubuklinggau city. The method used is a quantitative approach by applying the Granger causality model and multiple linear regression. The findings of this study indicate that regional revenues (hotel tax, restaurant tax and market retribution) does not Granger cause to economic growth, the fact otherwise shows that economic growth is able to cause regional revenues (hotel tax, restaurant tax and market retribution). Other findings indicate that hotel tax (X1) and restaurant tax (X2) do not have a significant effect on economic growth in the trade, hotel and restaurant sector. Whereas for market retribution (X3) it has a significant influence on economic growth in the trade, hotel and restaurant sector. This means that regional revenues through hotel and restaurant taxes have not been able to create economic growth in the trade, hotel and restaurant sector in Lubuklinggau City